Nuclear gene dosage effects upon the expression of maize mitochondrial genes. - Auger, D L (2001)
Each mitochondrion possesses a genome that encodes some of its own components. The nucleus encodes most of the mitochondrial proteins, including the polymerases and factors that regulate the expression of mitochondrial genes. Little is known about the number or location of these nuclear factors. B-A translocations were used to create dosage series for 14 different chromosome arms in maize plants with normal cytoplasm. The presence of one or more regulatory factors on a chromosome arm was indicated when variation of its dosage resulted in the alteration in the amount of a mitochondrial transcript. We used quantitative Northern analysis to assay the transcript levels of three mitochondrially encoded components of the cytochrome c oxidase complex (cox1, cox2, and cox3). Data for a nuclearly encoded component (cox5b) and for two mitochondrial genes that are unrelated to cytochrome c oxidase, ATP synthase alpha-subunit and 18S rRNA, were also determined. Two tissues, embryo and endosperm, were compared and most effects were found to be tissue specific. Significantly, the array of dosage effects upon mitochondrial genes was similar to what had been previously found for nuclear genes. These results support the concept that although mitochondrial genes are prokaryotic in origin, their regulation has been extensively integrated into the eukaryotic cell.